2015
DOI: 10.1007/s00464-015-4597-8
|View full text |Cite
|
Sign up to set email alerts
|

What do residents need to be competent laparoscopic and endoscopic surgeons?

Abstract: These data indicate that both residents and faculty perceive significant competency gaps for both laparoscopy and flexible endoscopy, with the most notable shortcomings for advanced and therapeutic cases, respectively. Improvement in resident training methods in these areas is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…These results support findings in the literature of variability in competency and confidence in performing flexible endoscopy among graduating general surgery residents [5][6][7]. Despite having completed a residency program in general surgery and two full months of fellowship, results indicate that the majority of trainees in this sample felt less than ''somewhat confident'' performing any endoscopic procedures aside from placement of a percutaneous endoscopic gastrostomy (PEG) tube or performing diagnostic EGD and colonoscopy.…”
Section: Discussionsupporting
confidence: 85%
“…These results support findings in the literature of variability in competency and confidence in performing flexible endoscopy among graduating general surgery residents [5][6][7]. Despite having completed a residency program in general surgery and two full months of fellowship, results indicate that the majority of trainees in this sample felt less than ''somewhat confident'' performing any endoscopic procedures aside from placement of a percutaneous endoscopic gastrostomy (PEG) tube or performing diagnostic EGD and colonoscopy.…”
Section: Discussionsupporting
confidence: 85%
“…Although studies examining clinical performance in endoscopy have revealed no differences among general surgeons, colorectal surgeons, and gastroenterologists (GI) [5], the education of surgical residents in flexible endoscopy has come under increased scrutiny [6]. In addition, general surgery residents are expressing concerns about their ability to perform endoscopy upon graduation [7,8] and many residency program directors are experiencing difficulties in providing trainees with an adequate flexible endoscopy curriculum [9].…”
mentioning
confidence: 98%
“…Since then several initiatives have been proposed to improve training in MIS and to transfer learning curves out of the operating room [12]. Not only (bi)manual dexterity and hand-eye coordination, but also handling long instruments that amplify tremors, dealing with the fulcrum effect and reduced tactile feedback should be mastered to perform laparoscopic surgery safely [13, 14]. …”
mentioning
confidence: 99%
“…If laparoscopic experience is acquired in theater without preclinical training, it will have negative effects on learning curves and self-confidence will establish slowly, because residents are not comfortable due to a lack of competence [14]. Moreover, there is a higher risk for complications if the novice attains basic laparoscopic skills in a patient model [15].…”
mentioning
confidence: 99%